1975
DOI: 10.1530/jrf.0.0420277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Freezing Temperature, Addition of Glycerol and Dilution on the Survival and Fertilizing Ability of Deep-Frozen Ram Semen

Abstract: The influence oftemperature, addition of glycerol, initial freezing temperature, method of dilution, level of glycerol in the diluted semen, equilibration time and type of diluent on the survival and fertilizing capacity of deep-frozen according to the best conditions was compared with that of "fresh" semen. The addition of glycerol at plus30 degrees C resulted in a highly significant decrease in the mean proportion of motile spermatozoa immediately after thawing compared with the effect of addition at plus 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 9 publications
1
42
0
1
Order By: Relevance
“…However, in vitro tests done on semen are not always related to the fertility of semen in vivo (Colas 1975;Tardif et al 1999). It is possible that the impact of glycerol is within the female genital tract.…”
Section: Effect Of Glycerol On Fresh Semenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vitro tests done on semen are not always related to the fertility of semen in vivo (Colas 1975;Tardif et al 1999). It is possible that the impact of glycerol is within the female genital tract.…”
Section: Effect Of Glycerol On Fresh Semenmentioning
confidence: 99%
“…Colas (1975) suggested that glycerol is slightly toxic to ram spermatozoa and that its negative effects could be reduced by its addition at a temperature near 0°C. Contrary to this recommendation, Salomon (1968) [reviewed by Salomon and Maxwell (2000)] reported that a single dilution of semen with an extender containing glycerol was as effective as a two-step dilution.…”
mentioning
confidence: 99%
“…Glycerol has been widely utilized as a cryoprotectant for frozen storage of spermatozoa of several mammals, including bull (Polge & Rowson, 1952), a dog (Seager, 1969), sheep (Colas, 1975), horse (Nishikawa et al, 1968) and pig (Pursel & Johnson, 1975 Graham et al, 1978). In that study, mouse epididymal spermatozoa were suspended in a skim milk medium (10-5% solids) containing 0-75% fructose, 1% bovine serum albumin and 4mM-calcium chloride and then frozen.…”
Section: Discussionmentioning
confidence: 99%
“…Since Polge & Rowson (1952) first reported that glycerol could provide considerable protection to bull spermatozoa during freezing and thawing, there have been many reports on the cryopreservation of spermatozoa of various species including horse (Nishikawa et al, 1968), pig (Pursel & Johnson, 1975), sheep (Colas, 1975), dog (Seager, 1969), rabbit (Fox, 1961), mouse (Graham et al, 1978, review), and man (Bunge & Sherman, 1953). Such reports are limited to relatively large animals;…”
Section: Introductionmentioning
confidence: 99%
“…Ejaculated and epididymal sperm samples stored at 4°C were cryopreserved in 0.25 ml straws according to method of Colas (Colas, 1975). For both species, sperm was cryopreserved with skim milk diluent at a concentration of 100 × 10 6 spz/straw for Ile de France rams and 60 × 10 6 spz for Corriedale rams.…”
Section: Fernández Abella Da Costa Guérin and Dacheuxmentioning
confidence: 99%